(untitled) (International Journal of Food and Nutritional Sciences, 2022)
While maintaining professional development approaches is difficult, it is a key priority for supporting the progress of teachers. We look at the degree to which teachers continued lesson study in their own schools following a four-year participation in a cross-school Lesson Study Professional Learning Network, as well as how they went about doing so. Diverse perspectives emerged about the general notion of lesson study. If the underlying idea was changed, teachers rarely continued with lesson study; when they did, they usually made adjustments that involved removing crucial elements. Instructors who upheld the fundamentals of lesson study were more likely to continue using the program in their own classrooms and to think highly of it.